Systematic Exposition of Mesenchymal Stem Cell for Inflammatory Bowel Disease and Its Associated Colorectal Cancer. (26th December 2018) - Kang, Jingjing; Zhang, Li; Luo, Xiao; Ma, Xiangyu; Wang, Gaoying; Yang, Yanhui; Yan, Yongmin; Qian, Hui; Zhang, Xu; Xu, Wenrong; Mao, Fei
Abstract : Mesenchymal stem cells (MSCs) therapy has been applied to a wide range of diseases with excessive immune response, including inflammatory bowel disease (IBD), owing to its powerful immunosuppression and its ability to repair tissue lesions. Different sources of MSCs show different therapeutic properties. Engineering managements are able to enhance the immunomodulation function and the survival of MSCs involved in IBD. The therapeutic mechanism of MSCs in IBD mainly focuses on cell-to-cell contact and paracrine actions. One of the promising therapeutic options for IBD can focus on exosomes of MSCs. MSCs hold promise for the treatment of IBD-associated colorectal cancer because of their tumor-homing function and chronic inflammation inhibition. Encouraging results have been obtained from clinical trials in IBD and potential challenges caused by MSCs therapy are getting solved. This review can assist investigators better to understand the research progress for enhancing the efficacy of MSCs therapy involved in IBD and CAC.